Orientation-specific amorphization and intercalated recrystallization at ion-irradiated SrTiO3/MgO interfaces. Issue 16 (28th August 2014) - Aguiar, Jeffery A.; Zhuo, Mujin; Bi, Zhenxing; Fu, Engang; Wang, Yongqiang; Dholabhai, Pratik P.; Misra, Amit; Jia, Quanxi; Uberuaga, Blas P.
Abstract: Abstract : Oxide composites are a class of materials with potential uses for nuclear, space, and coating applications. Exploiting their promise, however, requires a detailed understanding of their interfacial structure and chemistry. Using analytical microscopy, we have examined the radiation damage behavior at the interface of a model oxide bilayer, SrTiO3 /MgO. The as-synthesized SrTiO3 thin film contained both (100) and (110) oriented domains. We found that after ion beam implantation the (110) domains amorphized at a lower radiation fluence than the (100) domains. Further, a persistent crystalline layer of SrTiO3 forms at the interface even as the rest of the SrTiO3 film amorphizes. We hypothesize that the enhanced amorphization susceptibility of the (110) domains is a consequence of how charged irradiation-induced defects at the interfaces interact with the charged planes of the (110) domains. These results demonstrate the complex relationship between interfacial structure and radiation damage evolution at oxide interfaces.